2013
DOI: 10.1063/1.4801660
|View full text |Cite|
|
Sign up to set email alerts
|

Core hole screening and decay rates of double core ionized first row hydrides

Abstract: Because of the high intensity, X-ray free electron lasers allow one to create and probe double core ionized states in molecules. The decay of these multiple core ionized states crucially determines the evolution of radiation damage in single molecule diffractive imaging experiments. Here we have studied the Auger decay in hydrides of first row elements after single and double core ionization by quantum mechanical ab initio calculations. In our approach the continuum wave function of the emitted Auger electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…They found that the nuclear motion of the K −2 state affects the Auger spectrum. Subsequently they computed the Auger decay rates of the K −2 states in a sequence of isoelectronic first-row hydrides, and showed that the rates of the double core-holes are more than twice those of the single core holes [57]. This rate enhancement for DCH was attributed partly to an increased valence population in the vicinity of the core-holes.…”
Section: History Of the Theoretical Study Of Molecular Dch Statesmentioning
confidence: 99%
“…They found that the nuclear motion of the K −2 state affects the Auger spectrum. Subsequently they computed the Auger decay rates of the K −2 states in a sequence of isoelectronic first-row hydrides, and showed that the rates of the double core-holes are more than twice those of the single core holes [57]. This rate enhancement for DCH was attributed partly to an increased valence population in the vicinity of the core-holes.…”
Section: History Of the Theoretical Study Of Molecular Dch Statesmentioning
confidence: 99%
“…[11], refers to double-core-hole (DCH) spectroscopy. Since the lifetimes of the DCH states can be significantly shorter than the lifetimes of the corresponding single-core-hole states (SCHs) [12][13][14][15], one can expect a considerable reduction of the nuclear dynamics in DCH states. However, as we have recently shown, strongly dissociative potential-energy surfaces of molecular DCH states may provide for a substantial nuclear dynamics [15] and may even lead to an ultrafast dissociation [16].…”
Section: Introductionmentioning
confidence: 99%
“…´-2.2 10 3 . Furthermore, comparison of linewidths of the L-MM Auger and LL-MMM CAD signals showed that the double L-vacancy state decays more than two times faster compared to a single L-vacancy, similarly to double K-vacancy states [88,89]. From the full width at half maximum of the Lorentzian component in the Voigt profile fitted to the CAD spectral line, the decay rate of the LL D ( ) double vacancy state can be estimated as ´-5 10 s 14 1 , giving the CAD rate of the order of -10 s 12 1 .…”
Section: Experimental Evidence For Collective Auger Decay In Atomsmentioning
confidence: 99%